Developing a palm oil sector: The experiences of Malaysia and Ghana compared - Niels Fold; Lindsay Whitfield (Danish Institute for International Studies (DIIS), 2012)
This paper explores what can be learned about the development of a productive sector and the factors that affect the process of upgrading and innovation, through a comparative assessment of the experiences of Malaysia and Ghana in the palm oil sector. The purpose is not to carry out a direct comparison of the trajectories of the sectors in the two countries, which would serve only to emphasize the failures in the 'construction' of the palm industry in Ghana. Rather, the role of context must be acknowledged, such that learning starts with understanding key points in the industries' trajectories that either break or accelerate path dependency. Thus, the paper focuses on the differing contextual factors and initial conditions, and how they shaped early divergent paths and industry structures, as well as the presence or absence of factors supporting expansion and diversification within each country's trajectory.
Keywords: 300; Palmöl; Agrarproduktion; Wirtschaftsförderung; Ghana; Malaysia